Crack capitalism - Holloway, John, 1947- (Pluto Press ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2010)
'Crack Capitalism' argues that radical change can only come about through the creation, expansion and multiplication of 'cracks' in the capitalist system.